The Impact of Retention Strategies on the Performance of Teachers in Private Secondary Schools: A Case of Dodoma City, Tanzania - Daud N. Mollel; Malkia Rhodes Moshi (Eximia, 2024)
The presence of persistent needs for motivated teaching staff to uphold the standards of education at secondary schools poses a significant challenge concerning the retention of competent teachers in private secondary schools. Teacher turnover poses significant tests for educational establishments, affecting both the stability of the schools and the quality of education provided. Like other educational institutions, the prevailing competition to recruit and retain highly qualified teachers, private secondary schools face the problem of maintaining competent teachers within a context characterized by higher rates of staff turnover. This article is to provide a comprehensive theoretical evaluation of strategies to sustain teachers’ retention in private secondary schools by assessing the potential advantages associated with the implementation of effective retention measures. Moreover, the study probed into the existing literature to explore many retention features including, professional growth opportunities, organizational culture, leadership, and compensation to provide insights into the formulation of effective retention strategies to be applied by schools. By gaining a comprehensive understanding of the strategies, challenges, and potential outcomes, school management and educational policymakers can advance the efficacy, prosperity, and stability of learning environments for teaching staff and students. A cross-sectional survey design and the research approach combined both qualitative and quantitative paradigms. Simple random sampling (SRS) and purposive technic were used to draw a sample of eighty (80) respondents. SRS was adopted to interrogate teachers and purposive for key informants. Data analysis was employed by use of multiple responses, multiple linear regression, and analysis of variance (ANOVA). Salary, adequate learning facilities, a welcoming environment, and leadership style were identified as retention methods by the study’s findings. The survey, however, identified the following barriers to implementing teachers’ retention strategies including heavy workloads, lack of chances to advance, low pay and benefits, poor working conditions, and higher workplace stresses. Despite the outlined retention strategies, implementation matters including the lack of professional development opportunities, attractive incentive packages, and work-related benefits, unfavourable working conditions, and stress brought on by heavy workloads should be adequately addressed by school management and other decision-makers if they need to retain their valuable talented teachers.